2004
DOI: 10.1073/pnas.0400060101
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism for affinity maturation of an anti-lysozyme antibody

Abstract: In the immune response against a typical T cell-dependent protein antigen, the affinity maturation process is fast and is associated with the early class switch from IgM to IgG. As such, a comprehension of the molecular basis of affinity maturation could be of great importance in biomedical and biotechnological applications. Affinity maturation of anti-protein antibodies has been reported to be the result of small structural changes, mostly confined to the periphery of the antigen-combining site. However, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Comparison of the antibody complexes to the free structures of HyHEL63 crystallized in different space groups, showed minor conformational differences. Furthermore, no correlation was found between the amount of buried surface area or number of contacts and the observed affinity difference, albeit that such a correlation has been observed in the comparison of the structures of the antibodies D.44.1 and the more matured F10.6.6 in complex with HEWL (31). However, one should note that all these antibodies were already considerably matured and therefore might not represent early events in the maturation pathway.…”
Section: Discussionmentioning
confidence: 75%
“…Comparison of the antibody complexes to the free structures of HyHEL63 crystallized in different space groups, showed minor conformational differences. Furthermore, no correlation was found between the amount of buried surface area or number of contacts and the observed affinity difference, albeit that such a correlation has been observed in the comparison of the structures of the antibodies D.44.1 and the more matured F10.6.6 in complex with HEWL (31). However, one should note that all these antibodies were already considerably matured and therefore might not represent early events in the maturation pathway.…”
Section: Discussionmentioning
confidence: 75%
“…In some instances, the more flexible ''induced fit'' binding observed for germ-line clones was ''fixed'' in mutationmatured clones to give a ''lock-and-key'' mode of binding and, consequently, a higher binding affinity and specificity (7,8). Other groups have shown that improvements in shape-complementarity with antigen are responsible for increasing affinity and specificity (9,10). Much less research has focused on affinity maturation in ectothermic vertebrates.…”
Section: First Molecular and Biochemical Analysis Of In Vivo Affinitymentioning
confidence: 99%
“…Indeed, in silico design of mutations based on co-crystal structural analyses have shown that such new contacts can significantly enhance binding affinity in protein-protein (24) and protein-hapten interactions (25). In contrast, post hoc structural analyses of mutations generated naturally during B-cell development (26) or by Darwinian display-based evolution (27), have shown that considerable changes in binding energy can be achieved not by adding significant new contacts with antigen, but rather by "fine tuning" or "rigidification" of the antibody-antigen interface (28).…”
Section: Discussionmentioning
confidence: 99%